2020
DOI: 10.12688/f1000research.24818.1
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum β-lactamases and class C β-lactamases gene frequency in Pseudomonas aeruginosa isolated from various clinical specimens in Khartoum State, Sudan: a cross sectional study

Abstract: Background: Pseudomonas aeruginosa is a pathogenic bacterium, causing nosocomial infections with intrinsic and acquired resistance mechanisms to a large group of antibiotics, including β-lactams. This study aimed to determine the susceptibility pattern to selected antibiotics and to index the first reported β-lactamases gene (extended spectrum β-lactamases (ESBLs) genes and class C β-lactamases genes) frequency in Ps. aeruginosa in Khartoum State, Sudan. Methods: 121 Ps. aeruginosa clinical isolates from vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The unique feature of P. aeruginosa isolates is their ability to exhibit resistance to a variety of antibiotics, Amoxicillin CA and Amoxicillin were not an exception as the isolate demonstrated 100 % resistance. Similarly, Abdelrahman et al [33] confirmed P. aeruginosa isolates were resistant to Amoxicillin and Amoxyclav (100%). Ahmad et al [34] in Pakistan reported resistance to Amoxicillin and Amoxyclav was 73.4% and 67.7% respectively while similar reported in this study is in line with the pattern in earlier studies in Abakaliki, Nigeria [35] and in Malaysia [36].…”
Section: Discussionmentioning
confidence: 82%
“…The unique feature of P. aeruginosa isolates is their ability to exhibit resistance to a variety of antibiotics, Amoxicillin CA and Amoxicillin were not an exception as the isolate demonstrated 100 % resistance. Similarly, Abdelrahman et al [33] confirmed P. aeruginosa isolates were resistant to Amoxicillin and Amoxyclav (100%). Ahmad et al [34] in Pakistan reported resistance to Amoxicillin and Amoxyclav was 73.4% and 67.7% respectively while similar reported in this study is in line with the pattern in earlier studies in Abakaliki, Nigeria [35] and in Malaysia [36].…”
Section: Discussionmentioning
confidence: 82%